Critical analysis of the taxation of second-tier cooperatives as integration formula - Aguilar Rubio, Marina (REVESCO. Revista de Estudios Cooperativos, 2017)
Second-tier cooperatives are one of the basic instruments for business concentration in the cooperative law and the formula traditionally used by cooperatives when it comes to building an integration project. The work tries to show the special taxation of the second-tier cooperatives, that we are interested especially because it is the instrument of integration most used in Spain by cooperatives to undertake concentration processes in the agri-food field, key sector in our geographical environment. We will focus the study of its taxation in the Corporate Tax due to the tax peculiarities that it presents in this type of company. Second-tier cooperative societies may choose to tax as simple cooperative societies, as regulated in Law 20/1990, of December 19, on Cooperative Tax Regime, or to make as cooperative group, accepted in the special regime of consolidated taxation system established for this social type.